Características psicosociales que se relacionan con la ideación suicida en jóvenes universitarios del municipio de Roldanillo del Valle del Cauca. - Agudelo, Daniela; Osorio, Juan David (Psicología (Distancia), 2024)
The present research project is called psychosocial characteristics that are related to suicidal ideation in young residents in the municipality of Roldanillo (V), whose purpose is to know the emotional state of the evaluated subjects, the family relationships they have and the way in which the social environment is related to the presence of suicidal ideation. The theoretical foundations are focused on the study of the cognitive, emotional and identity development of young people, as well as the topic of suicidology and its respective risk factors. The methodology used is quantitative, non-experimental, cross-sectional, since it assesses the participants in a single moment, using the questionnaire to evaluate suicidal behavior, which allowed identifying that the respondents who express suicidal ideations or attempts usually come from dysfunctional homes, behavioral changes, history of self-injurious behaviors; being the female gender the one that presents history of family members with suicidal behaviors and it stands out that the frequency of self-harm attempts was higher in men.